Incentives for nature conservation in urban landscapes - Irene Ring; Karin Frank; Georg Kneer (UFZ-Umweltforschungszentrum Leipzig-Halle, 1998)
The aim of this article is to contribute to the development of ecological-economic incentives in conservation policy. Our approach uses strategies for establishing habitat networks as an example to develop spatially-oriented incentives in urban landscapes. The incentives should ideally consider aspects both of ecological effectiveness and economic efficiency. Our understanding of ecological-economic incentives reaches beyond this stage: not only must economic incentives in environmental policy be based on ecological knowledge, but also, they have to consider social aspects of implementation and acceptance. The ecological analysis of strategies for species protection in urban landscapes leads to management recommendations as a basis for the specification of environmental policy goals. Based on ecological knowledge, which shows where to invest scarce resources, the economic perspective aims at analysing and evaluating environmental policy instruments for their suitability and efficiency. The ecological and economic research is to be combined with a sociological approach, which investigates the choice and application of environmental policy measures as a system of social action. The analysis of problems of implementation and acceptance will be used to support the introduction of new instruments or to improve existing incentive systems related to nature conservation in urban landscapes. For this purpose, a survey was carried out on the use of environmental policy instruments (regulation, planning, economic incentives, communication, information) in German cities in 1997. Furthermore, two existing economic instruments in German nature protection policy are analysed in detail: the compensation charge as part of the impact regulation and incentive programmes on the level of the German federal states that offer financial incentive measures for nature protection.
Keywords: 330